2012
DOI: 10.1136/archdischild-2012-301885.1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in paediatric coeliac disease 1990-2009: a UK regional retrospective audit of cases

Abstract: Aim To review all incident cases of paediatric coeliac disease (CD) in a UK region over the 20 year period from 1990-2009; to observe trends in incidence, symptom presentation, age at diagnosis and the impact of active screening of at-risk groups; and to audit laboratory results at diagnosis for 01/2005-12/2009. Methods We performed a retrospective audit of case notes, pathology databases, endoscopy and electronic patient records for all children under 16 years diagnosed with CD on duodenal biopsy between 01/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There is significant evidence from groups who have studied a variety of chronic diseases that those parents with higher socio‐economic status have more health seeking behaviours than those in lower socio‐economic status groups . Indeed, we know that there is an increasing incidence of children presenting with mild abdominal symptoms , and so it may be possible to suggest that the parents of children in high socio‐economic status areas are more likely to seek advice for minor symptoms of coeliac disease, such as mild abdominal pain than parents who have a lower socio‐economic status. Equally, it is possible that children of high socio‐economic status are more likely to be presented for serological screening if a first degree relative has been diagnosed than in those families from lower socio‐economic status groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is significant evidence from groups who have studied a variety of chronic diseases that those parents with higher socio‐economic status have more health seeking behaviours than those in lower socio‐economic status groups . Indeed, we know that there is an increasing incidence of children presenting with mild abdominal symptoms , and so it may be possible to suggest that the parents of children in high socio‐economic status areas are more likely to seek advice for minor symptoms of coeliac disease, such as mild abdominal pain than parents who have a lower socio‐economic status. Equally, it is possible that children of high socio‐economic status are more likely to be presented for serological screening if a first degree relative has been diagnosed than in those families from lower socio‐economic status groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an unpublished PhD from the Sheffield/Nottingham area found that incidence rate of coeliac disease in adults was twice as high in the least deprived and most affluent quintiles (0.17/1000), compared with those with coeliac disease in the most deprived and poorest quintile (0.07/1000) . Other studies have found no difference between socio‐economic status .…”
Section: Aimmentioning
confidence: 97%
See 1 more Smart Citation